2020
DOI: 10.3389/fpsyg.2020.00328
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cynicism in Medical Students: Exploring the Role of Signature Character Strengths and Well-Being

Abstract: Reports of medical students experiencing burnout-related symptoms (e.g., cynicism) have increased in recent years. Little is known about the developmental process of this phenomenon and its relations with signature character strengths and well-being. The aim of this longitudinal analysis was to explore changes in the level of cynicism of medical students while in preclinical education. We further examined how the applicability of signature character strengths and well-being are related to this developmental pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 101 publications
2
18
0
8
Order By: Relevance
“…In addition, love of learning has also been found to relate to the educational level obtained in adults, hinting at its general relevance for education (Ruch et al, 2010). Kachel et al (2020) investigated the applicability of signature character strengths in studies and private life in a sample of medical students. Overall, they found higher scores for the applicability of signature character strengths in private life than for the applicability in university life, in particular for those students with high or increasing levels of cynicism.…”
Section: Educationmentioning
confidence: 99%
“…In addition, love of learning has also been found to relate to the educational level obtained in adults, hinting at its general relevance for education (Ruch et al, 2010). Kachel et al (2020) investigated the applicability of signature character strengths in studies and private life in a sample of medical students. Overall, they found higher scores for the applicability of signature character strengths in private life than for the applicability in university life, in particular for those students with high or increasing levels of cynicism.…”
Section: Educationmentioning
confidence: 99%
“…Relating to character strengths of medical students in terms of the VIA-classification ( Peterson and Seligman, 2004 ), eight empirical studies could be identified. Five studies derived from the ‘WELL-MED’ project (see section ‘Participants and Procedure’ for details) with two focusing on the applicability of character strengths and their associations with health-related outcomes ( Hausler et al, 2017a ; Huber et al, 2020 ), one illuminating the correlations of character strengths and different well-being aspects ( Hausler et al, 2017b ), one examining the development of cynicism ( Kachel et al, 2020a ), and one validating the VIA-120 short form ( Höfer et al, 2019 ). However, none of these studies focused on identifying a certain profile of medical students.…”
Section: Virtues and Character Strengths In The Literaturementioning
confidence: 99%
“…Additionally, they often report impaired well-being or even mental illness raising the question on possible underlying character strengths profiles. Medical students reported more depressive symptoms and higher levels of distress with regard to their health compared to the general United States population ( Dyrbye et al, 2014 ), impaired mental health (e.g., Brazeau et al, 2014 ) and well-being (e.g., Dunn et al, 2008 ), or early onset of burnout symptoms ( Kachel et al, 2020a ). Moreover, origins of recurrent physician burnout were identified with studies showing a prevalence of 45% up to 70% to have these symptoms during medical education at least once ( Dyrbye et al, 2008 ; Ishak et al, 2013 ) entailing health impairing consequences (e.g., Jackson et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…14 This could be due to a reduction in empathy and interest in working with the underserved as one progresses through their medical training accompanied by an increase in burnout, cynicism and negative attitudes towards homeless individuals. [15][16][17][18][19] Burnout is also more prominent for those training in surgical specialties, which could explain why there are more statistical differences in items between residents and medical students in this study compared to the study conducted with emergency medicine residents. 14,20 However, the aforementioned study did not include ophthalmologists in their analysis of burnout in surgical specialties, and it would be interesting to see if a similar conclusion would result if they were included.…”
Section: Discussionmentioning
confidence: 71%